2012
DOI: 10.1111/j.1440-1789.2012.01303.x
|View full text |Cite
|
Sign up to set email alerts
|

A case of unclassified high‐grade glioma with polar spongioblastoma pattern

Abstract: Primitive polar spongioblastoma was first described by Russell and Cairns in 1947. However, the polar spongioblastoma pattern is often seen in many neuroepithelial tumors, and this category was deleted in the previous World Health Organization (WHO) classification. In 2010, Nagaishi et al. reported on a case involving a neuroepithelial tumor with the typical histological pattern of polar spongioblastoma and suggested that this tumor might not be suited to any of the neuroepithelial tumors in the current WHO cl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
5
0

Year Published

2016
2016
2019
2019

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 11 publications
1
5
0
Order By: Relevance
“…The term "primitive polar spongioblastoma" is used for tumors not included in the new WHO classification and composed of cells with a specific palisading sequence. This pattern can be seen in PAs (e.g., the second resection specimen of our patient) 4) . Tihan and Burger 13) have defined pilomixoid astrocytoma, which is an aggressive subtype of PAs.…”
Section: Discussionsupporting
confidence: 60%
“…The term "primitive polar spongioblastoma" is used for tumors not included in the new WHO classification and composed of cells with a specific palisading sequence. This pattern can be seen in PAs (e.g., the second resection specimen of our patient) 4) . Tihan and Burger 13) have defined pilomixoid astrocytoma, which is an aggressive subtype of PAs.…”
Section: Discussionsupporting
confidence: 60%
“…This consideration was based on the similarity of the type of network and image data and which suggested that machine learning, and especially the CNN model, was suitable for the estimation of the individual brain network. 31,32 The high accuracy of the CNN model in image recognition and classification is based on three features; the convolution layer, multilayered neural network classifier part and a optimization by a back propagation method. 33,34 The convolution layer extracts the features of matrix data by multiple filters and the multilayer (deep) convolution can extract the high dimensional features and its output is transmitted to following multiple layer neural network.…”
Section: Discussionmentioning
confidence: 99%
“…Similarly, whole-brain or skull-base radiotherapy is often administered to patients with cranial neuropathies. [199][200][201][202][203][204][205][206][207][208][209][210] Radiotherapy is indicated for patients with bulky radiographic disease because the intra-CSF administration of chemotherapy is limited by diffusion to 2 to 3 mm of penetration into the tumor nodules. In addition, involved-field radiotherapy should be employed to correct abnormalities in CSF flow because normalizing CSF flow obstruction is associated with improvements in patient outcomes.…”
Section: Radiotherapymentioning
confidence: 99%
“…In addition, involved-field radiotherapy should be employed to correct abnormalities in CSF flow because normalizing CSF flow obstruction is associated with improvements in patient outcomes. [199][200][201][202][203][204][205][206][207][208][209][210] Rarely is whole-neuraxis ra-diotherapy used to treat neoplastic meningitis from solid tumors because of its association with significant levels of systemic toxicity (eg, severe myelosuppression, mucositis) and because it is not curative. [199][200][201][202][203][204][205][206][207][208][209][210] Chemotherapy Among all of the therapies used to manage neoplastic meningitis, chemotherapy is the single treatment modality used to treat the whole neuraxis, administered either intrathecally or systemically.…”
Section: Radiotherapymentioning
confidence: 99%
See 1 more Smart Citation